Analysis of the microstates of prolonged disorders of consciousness - Wu, Yuzhang; Feng, Shangang; Cui, Deqiu; Li, Zhongzhen; Qu, Ruowei; Cheng, Yifeng; Wang, Yangang; Yin, Shaoya; Feng, Keke (Frontiers in Neurology, 2025)
ObjectivesProlonged disorders of consciousness (pDOC) is a common disease in neurology. This study aimed to explore the microstate (MS) characteristics of pDOC patients based on resting-state Electroencephalography (EEG) and explore the changes in brain function in pDOC patients.MethodsPatients were divided into healthy group and pDOC group according to the presence of consciousness. The T1 weighted 3D magnetization pre-gradient echo sequence (3d-t1-mprage) and resting state video EEG data were collected. First, the microstate clustering analysis was carried out. The global field power (GFP) was used to calculate microstate indicators (Duration, Occurrence, and Coverage), and then the statistical analysis between groups was carried out. Finally, the original resting state EEG data were reconstructed according to the clustered microstate GFP peak, and the connectivity of the brain in the four microstates was calculated, respectively.ResultsThe topographic map of MS B in the DOC goup (DG) is different from that in the healthy goup (HG). The Coverage value of MS B (Z = −2.084, p = 0.037), the Occurrence value of MS D (Z = −2.141, p = 0.032), the Coverage value of MS D (Z = −1.999, p = 0.046) between the two groups has a significant difference. The MS B topographic map was significantly different between the two groups. The MS D of DG was significantly different from that of the HG. Only part of the connections were preserved.ConclusionThe microstate topographic maps of pDOC and CG are not identical. At the same time, the brain connectivity of pDOC patients in the four MS decreased significantly compared to the HG.